2018
DOI: 10.1002/mp.13125
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the DACS‐integrated Radiation Dose Monitor® skin dose mapping software using XRRV3 Gafchromic® films

Abstract: The accuracy of RDM's DACS-integrated skin dose mapping software was acceptable considering measurement uncertainties associated with Gafchromic films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 22 publications
(80 reference statements)
1
32
0
Order By: Relevance
“…Bordier et al 5 compared a calculation method that produces dose maps using Gafchromic XR‐RV3 films on an anthropomorphic phantom and found that doses agreed within better than 15% compared with the Gafchromic films. Using the Radiation Dose Monitor tool, Habib Geryes et al 3 accomplished average difference of 10 ± 7% and 9 ± 7% between the calculated and the measured PSD values for 34 test conditions performed on PMMA phantom using Siemens Artis Zee and GE Innova IGS interventional systems, respectively. Methodology to evaluate software described by Habib Geryes et al was used in study by Greffier et al 18 and it was found that average differences between the measured PSD by XR‐RV3 Gafchromic films and the calculated PSD using interactive Skin Dose Map® tool (SDMTool) integrated to the radiation dose management system (RDMS) DoseWatch® were 6% ± 6% (range from − 3% to 22%) for flat phantom and 5% ± 7% (range from − 3% to 25%) for ICRP phantom.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bordier et al 5 compared a calculation method that produces dose maps using Gafchromic XR‐RV3 films on an anthropomorphic phantom and found that doses agreed within better than 15% compared with the Gafchromic films. Using the Radiation Dose Monitor tool, Habib Geryes et al 3 accomplished average difference of 10 ± 7% and 9 ± 7% between the calculated and the measured PSD values for 34 test conditions performed on PMMA phantom using Siemens Artis Zee and GE Innova IGS interventional systems, respectively. Methodology to evaluate software described by Habib Geryes et al was used in study by Greffier et al 18 and it was found that average differences between the measured PSD by XR‐RV3 Gafchromic films and the calculated PSD using interactive Skin Dose Map® tool (SDMTool) integrated to the radiation dose management system (RDMS) DoseWatch® were 6% ± 6% (range from − 3% to 22%) for flat phantom and 5% ± 7% (range from − 3% to 25%) for ICRP phantom.…”
Section: Discussionmentioning
confidence: 99%
“…At the present time, most equipment vendors have developed online solutions for skin dose calculations. CareMonitor by Siemens and DoseWise by Philips are solutions which basically provide the accumulated peak air kerma in the current projection 3 . On the other hand, Dose Map from GE is an advanced two‐dimensional (2D) solution, 4–6 while Dose Tracking System (DTS) from Canon (Toshiba) represents a state of the art three‐dimensional (3D) solution for skin dose mapping 7–9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For different software applications validated on phantoms (PMMA, water or anthropomorphic phantom), the differences between calculated and measured doses range from 5% to 25% [27][28][29][32][33][34][36][37][38]. Most of these validations were performed only with a single field or in simple setups, for example using no more than four irradiation events and a limited number of beam projections, except for two recent studies that described a complete validation of their software [29,32]. Only two systems [33,34] were also validated on patients, and the calculated peak skin dose agreed with the measurements within 50% or more in the worst case.…”
Section: Dose Accuracymentioning
confidence: 99%
“…However, in those centers where software for skin dose map evaluation software is not available or for older equipment, K a,r and KAP remain useful PSD estimators [19]. It is possible to evaluate the PSD through different methods of direct measurements including thermoluminescent dosimeters (TLDs) [20], semiconductor dosimeters [21], MOSFETs [22] and radiochromic films procedures using offline tools such as RDM by MedSquare [29], DOSE by Qaelum [30], the DIDo system implemented in the software DOLIR [31], Skin Dose Map® tool integrated in DoseWatch® by GE Healthcare [32], em.dose from Esprimed [33,34], OpenSkin software provided by the OpenREM project [35], the UF-RIPSA algorithm developed at the University of Florida [36], the software developed by the Mayo Clinic [37], and two software (FDEIR and MC-GPU), based on Monte Carlo simulations [38]. These software can provide a dose map and the PSD value retrospectively; some of them are integrated into Radiation Dose Index Monitoring (RDIM) systems [29][30][31][32] and others are stand-alone products [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%